Critical factors for developing brand equity: an empirical investigation in Malaysia - Silva, Suranga; Nikhashemi, Seyed Rajab; Haque, A. K. M. Ahasanul; Yasmin, Farzana; Khatibi, Ali (International Organization of Scientific Research (IOSR), 2012)
The power of branding is most often powerful than the product itself. Renowned brands like Procter and Gamble paid Richardson-Vicks 2.6 times of its book value. Nabisco was sold for 3.2 times of its book value and General Motors was sold for 3.5 times its book value. Whilst these corporations succeeded in using their brand as a source for their company's worth, others lagged behind, trying to comprehend the real value of branding. This study draws upon past literatures in branding and proposes the use the brand equity concept towards formulating a meaningful plat for a Malaysian Internet service called TMnet, Jaring and Maxis to nest. This study develops a brand equity construct which nestles upon brand concept of functionality, image, perceived quality and brand loyalty. Developing brand equity is not an easy task. Therefore, this study tries to identify the important factors for creating brand equity. Results of this study shows that perceived quality is the most important factor for developing brand equity. The results of this study confirm the significant influence of these four utmost important factors on brand equity. In conclusion, practitioners can derive a better understanding of the activities that are undertaken by these organizations and how the way these activities are being dealt with. Keywords: Functionality, image of brand, perceived quality of brand and brand loyalty